Pengaruh Perceived Quality, Perceived Value, dan Ekuitas Merek terhadap Loyalitas Pelanggan McDonald’s dengan Kepuasan Pelanggan sebagai Variabel Moderasi - Hababa, Nabhan Rusmani; Mutmainah, Isbandriyati; Mulia, Agus Prana (Jurnal EMT KITA, 2025)
This study aims to examine the impact of perceived quality, perceived value, and brand equity on consumer loyalty, with satisfaction serving as a moderating variable among McDonald’s patrons in Bogor City. The population of this study consists of all McDonald's consumers in Bogor City, while the research sample is a subset of this population, obtained through the accidental sampling method. Data were collected by distributing online questionnaires through Google Forms to selected respondents. The study’s dependent variable is loyalty, whereas the independent variables include perceived quality, perceived value, and brand equity. The satisfaction variable was selected as the suspected moderator of the effects of perceived quality, perceived value, and brand equity on loyalty. The Moderated Regression Analysis (MRA) technique was employed utilising SPSS 25 software. With 150 respondents, the results of this study indicate that perceived quality, perceived value, and brand equity have a positive and significant partial effect on loyalty. The MRA test results indicate that the satisfaction variable effectively moderates the impact of perceived quality, perceived value, and brand equity on loyalty to McDonald’s. The F-test results indicate that perceived quality, perceived value, and brand equity simultaneously have a positive and significant effect on loyalty.